The Festival of Britain a land and its people - Atkinson, Harriet (I.B.Tauris & Co. ; Distributed in the United States by Palgrave Macmillan, 2012)
The Festival of Britain in 1951 transformed the way people saw their war-ravaged nation. Giving Britons an intimate experience of contemporary design and modern building, it helped them accept a landscape under reconstruction, and brought hope of a better world to come. Drawing on previously unseen sketches and plans, photographs and interviews, The Festival of Britain: A Land and Its People travels beyond the Festival's spectacular centrepiece at London's South Bank, to show how the Festival made the whole country an exhibition ground with events to which hundreds of the country's greatest architects, artists and designers contributed. It explores exhibitions in Poplar, Battersea and South Kensington in London; Belfast, Glasgow and Wales; a touring show carried on four lorries and another aboard an ex-aircraft carrier. It reveals how all these exhibitions and also plays, poetry, art and films commissioned for the Festival had a single focus: to unite 'the land and people of Britain'.